Implementation of Forest Area Regulation and Environmental Justice Challenges in Indonesia under Presidential Regulation No. 5 of 2025 - Agus Surono; Sadino Sadino; Zaitun Abdullah; Agung Iriantoro; Adnan Hamid; Maslihati Nur Hidayati (PT. Global Research Collaboration, 2025)
Background: Indonesia’s forest governance continues to face challenges such as overlapping land claims, agrarian conflicts, and institutional fragmentation. Presidential Regulation No. 5 of 2025 establishes a cross-sectoral Forest Area Order and Enforcement Task Force (PKH Task Force) to accelerate forest recovery and improve legal certainty. However, concerns remain regarding data reliability and social justice in its implementation. Objective: This study examines the implementation of forest area regulation under Presidential Regulation No. 5 of 2025, focusing on governance effectiveness, socio-ecological impacts, and the relationship between enforcement mechanisms and environmental justice. Methods: A qualitative socio-legal approach was employed, combining normative juridical analysis, focus group discussions, field observations, and comparative policy review. Data were analyzed using thematic content analysis and cross-case comparison. Results: Findings show that the PKH Task Force recovered approximately 3.3 million hectares of forest land by September 2025. Despite this achievement, structural issues persist, including inconsistent spatial data, overlapping customary land claims (17.6–24.4 million hectares), and unequal enforcement between large-scale actors and smallholders. Limited community participation has contributed to ongoing socio-ecological tensions. In contrast, participatory schemes such as PPTPKH/TORA (3.04 million hectares) and social forestry programs (4.1 million hectares involving over 800,000 households) indicate more inclusive governance outcomes. Conclusion: Forest governance reform demonstrates strong administrative performance but limited social legitimacy. Effective implementation requires integrating distributive, procedural, and restorative justice principles supported by participatory and integrated data governance systems. Limitations: The study is based on secondary data and selected qualitative cases, which may not fully represent regional variations in Indonesia